Perbedaan Efektivitas Penggunaan Media Belajar Video dan Modul Keterampilan Keperawatan dalam Pencapaian Kompetensi Pemasangan Kateter Urine - Kustanti Cecilya (Jurnal Keperawatan Notokusumo, 2013)
Background: The process of learning in nursing education institutions of learning include lectures and laboratory practice in nursing. The success of the laboratory learning process is influenced by the use of learning media. So far the teaching practicum in Nursing Academy Notokusumo media using the book module skills. From the evaluation of learning there are some skills that result was not optimal, such as urinary catheterization skill. Hence the need for instructional media innovations better. Objectives: The aim of this study was to determine differences in the effectiveness of the use of video and media learning modules nursing skills in the achievement of competence in the urine catheter Nursing Academy students Notokusumo Yogyakarta. Methods: This study is a research Randomized Controlled Trial, using the intervention group and control group. The number of respondents within each group of 15 students. The study was conducted in Notokusumo Nursing Academy on 25 May to 1 July 2012. Analysis of test data used is the t. Results: From the result showed that the data is known in the intervention group showed an increase in the average value significantly between before and after treatment, ie from 61.53 to 83.4. Judging from the paired t-test test results obtained at 0.011 p value, so there is known to significantly influence the use of video learning media.